Clinical features, surgical treatment, and outcome of intracranial aneurysms associated with moyamoya disease. (October 2020) - Ge, Peicong; Ye, Xun; Zhang, Qian; Liu, Xingju; Deng, Xiaofeng; Zhao, Meng; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Jizong
Highlights: Hemorrhage was the most common symptom. Revascularization surgery may prevent the rupture of intracranial aneurysms. Abstract: The objective of this study was to elucidate the clinical features, surgical treatment, and outcome of intracranial aneurysms associated with moyamoya disease. We retrospectively reviewed a consecutive cohort of 79 moyamoya disease patients with 98 intracranial aneurysms at Beijing Tiantan Hospital. Clinical features, radiological findings, and outcomes were analyzed. Prevalence of intracranial aneurysms in patients with moyamoya disease was 3.9%. The mean age at diagnosis was 39.0 ± 12.4 years, with 1 peak distribution in patients from 40 to 50 years of age. The ratio of women to men was 1.00:1.03. Familial occurrence was 2.5%. The initial symptom was hemorrhage or ischemia in 56 (70.9%) and 23 patients (30.4%), respectively. Most patients presented with Suzuki stage 3 or 4. Seventy-nine cases had 98 aneurysms. Of the 98 aneurysms, sixteen aneurysms (16.3%) were treated by microsurgery and 7 by endovascular procedures, 13 aneurysms were conservatively managed, the remaining 62 were treated with revascularization alone. After a median nine-month angiographic follow-up, 18 aneurysms received clipped or embolized were completed occlusion, 18 aneurysms received conservative treated or coating were remained stable. Of the remaining 63 aneurysms that were treated with revascularization alone, 59 of 63 aneurysms remained stable, and 2 were obliterated, whereas 1 aneurysm ruptured during the follow-up. Hemorrhage was the most common symptom in intracranial aneurysms associated with moyamoya disease. Revascularization surgery may improve cerebral circulation, decreases hemodynamic stress and prevent the rupture of intracranial aneurysms.